2022
DOI: 10.3390/ijms23031581
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-Disrupting Chemicals and Their Adverse Effects on the Endoplasmic Reticulum

Abstract: There is growing concern regarding the health and safety issues of endocrine-disrupting chemicals (EDCs). Long-term exposure to EDCs has serious adverse health effects through both hormone-direct and hormone-indirect ways. Accordingly, some EDCs can be a pathogen and an inducer to the susceptibility of disease, even if they have a very low affinity on the estrogen receptor, or no estrogenic effect. Endoplasmic reticulum (ER) stress recently attracted attention in this research area. Because ER and ER stress co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Accumulating evidence suggests that some endocrine disruptors induce ER stress, which might lead to apoptosis in a variety of models [27]. We measured the protein expression of two ER stress markers, namely immunoglobulin heavy chain-binding protein (BiP) and the phosphorylated form of the eukaryotic initiation factor-2α (p-eIF2α), in αTC1-9 cells treated with each of the six chemicals for 24 h. Exposure to 1 μM BPA reduced BiP expression by 45%, while no changes were observed in p-eIF2α levels (Figure 4A-C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidence suggests that some endocrine disruptors induce ER stress, which might lead to apoptosis in a variety of models [27]. We measured the protein expression of two ER stress markers, namely immunoglobulin heavy chain-binding protein (BiP) and the phosphorylated form of the eukaryotic initiation factor-2α (p-eIF2α), in αTC1-9 cells treated with each of the six chemicals for 24 h. Exposure to 1 μM BPA reduced BiP expression by 45%, while no changes were observed in p-eIF2α levels (Figure 4A-C).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence suggests that some endocrine disruptors induce ER stress, which might lead to apoptosis in a variety of models [27]. We measured the protein expression of two ER stress markers, namely immunoglobulin heavy chain-binding protein (BiP)…”
Section: Exposure To Different Mdcs Does Not Induce Er Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoplasmic reticulum stress activates a signaling network called the unfolded protein response (UPR) to restore endoplasmic reticulum homeostasis. However, under prolonged and severe endoplasmic reticulum stress by EDCs, the UPR can become cytotoxic [ 14 , 31 ].…”
Section: Brief Properties Of Edcsmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress has been shown to contribute in defective spermatogenesis in both animal models and humans ( 105 ). Several studies have reported a significant increase in ROS in infertile men compared to fertile men ( 105 , 106 ).…”
Section: Physiological Effects Of Edcs On Male Infertilitymentioning
confidence: 99%